2021
DOI: 10.1007/s13202-020-01059-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrating risk management concepts into the drilling non-productive time

Abstract: Introducing the non-productive time (NPT) concepts in the 1960s was a necessity dictated by the ever-increasing cost and complexity of the oil and gas well drilling. The NPT definition stayed unsettled until two decades later, the definition converged toward its accepted current definition of “the time when planned or out-of-plans drilling-related activities do not add value to the operation objectives.” NPT as it is defined in drilling nowadays is a form of time waste or loss which adversely impacts the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…This means that there is an urgent need for new quality Figure (6) shows that the percentage of NPT is about 34%, it is considered a significant proportion and is very costly in terms of time and money, and most of this is due to poor selection of drilling rigs, and that most of them were used to drill previous wells. The most common drilling problems comprise pipe sticking, missing rotation, hole skew, pipe failure, well instability, mud contamination, formation damage, hole clean-up, H2S bearing formation and shallow gas, and equipment and personnel problems as illustrated in Figure (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that there is an urgent need for new quality Figure (6) shows that the percentage of NPT is about 34%, it is considered a significant proportion and is very costly in terms of time and money, and most of this is due to poor selection of drilling rigs, and that most of them were used to drill previous wells. The most common drilling problems comprise pipe sticking, missing rotation, hole skew, pipe failure, well instability, mud contamination, formation damage, hole clean-up, H2S bearing formation and shallow gas, and equipment and personnel problems as illustrated in Figure (7).…”
Section: Resultsmentioning
confidence: 99%
“…Existence of drilling problems lead to postponement frequently push drilling action overdue the schedule [6]. The incidence of NPT and imperceptible lost time not only reason for undervalued finances but also consequence in postponements of the hydrocarbon production [7]. It was revealed that NPT can be avoided by using and following an optimal drilling program that includes all the drilling process, including equipment and personnel [8].…”
Section: Introductionmentioning
confidence: 99%
“…Konsep nonproductive time dimulai pada tahun 1960-an dan sejak saat itu banyak penelitian dan pendekatan muncul dalam upaya untuk mengendalikan waktu yang hilang ke nilai yang diterima. [4] [5] Nonproductive time tidak memiliki definisi standar. Setiap organisasi mendefinisikan non productive time dengan cara yang sesuai dengan tujuan mereka.…”
Section: Gambar 1 Tahap Utama Dari Proses Workover [3]unclassified
“…Minimising the drilling cost can be achieved by optimising the controllable drilling parameters such as WOB, revolutions per minute, and flow rate (FR) on the ROP (Bani et al, 2021). Barakat et al (2021) aimed to integrate Risk Management (RM) techniques with the philosophy of Non-Productive Time (NPT), along with other concepts such as Systems Thinking, Synergy, Continuous Improvement, and Total Quality. They developed a Java software model that represented NPT as an undesired event with a probability of occurrence, using RM terminology.…”
Section: Drilling Time Reductionmentioning
confidence: 99%